Dynamics of Service Trade in Association of Southeast Asian Nations: Process Towards Integration - Fadhil, Arkan; Hastiadi, Fithra Faisal (International Journal of Economics and Financial Issues, 2017)
Over the past few decades, Association of Southeast Asian Nations (ASEAN's) economic structure has continued to change. Overall, ASEAN's economic structure has shifted towards the service sector in line with the growing importance of this sector in the economy. This structural shift is very rapid along with the growing importance of the role of the service sector in supporting the agricultural sector and the manufacturing sector. Therefore, it is important to conduct further researches in the dynamics of service trade in ASEAN in achieving integration. This study focuses on the openness of ASEAN countries to trade. Openness as a basic component in the integration process is analyzed through a set of trade policies made as well as the complexity and depth of commitment in service trade agreements. The database used covers all ASEAN countries during the 2005-2014 timeframe. This study employs a descriptive analysis as the main approach, supported by fixed effect model to see the factors which contribute to the openness of ASEAN countries. The results of this study indicate that the openness of service trade in ASEAN is influenced by a set of limiting and facilitating policies. In addition, the complexity and depth of commitment play a role in influencing the openness of service trade. In the interim, variables of trade volume, population, real effective exchange rate, service trade facilities, and human capital contribute significantly to the openness of service trade in ASEAN. It can therefore be construed that the openness of service trade is determined by the policy instruments and commitments in the service trade agreements made. Keywords: Association of Southeast Asian Nations, Integration, Openness, Trading Services, Service Sector JEL Classifications: F10, F14, F15